Association of level of IL-6, IL-10, IL-18, tumour necrosis factor-α with rheumatic mitral stenosis and subsequent pulmonary hypertension - Tripathi, Gaurav; Mehta, Vimal; Trehan, Vijay (International Journal of Advances in Medicine, 2022)
Background: Objective of the study was to provide insight on the immune response in patients of rheumatic heart disease, mitral stenosis and evaluation of various cytokines in pulmonary hypertension secondary to rheumatic heart disease. Methods: Total 163 subjects, more than 18 year of age, were enrolled in this study. 84 subjects with rheumatic mitral stenosis (group A) diagnosed on two-dimensional echocardiography (2D echo) and 79 normal healthy volunteers (group B). Patients with mitral stenosis were further divided into subgroups based on severity of mitral stenosis [mitral valve area (MVA >1 cm2 and MVA <1 cm2) (subgroup Aa and Ab)] and presence or absence of pulmonary hypertension [pulmonary arterial systolic pressure (PASP >36 mm Hg) (subgroup Ac and Ad)]. Interleukins IL-6, IL-10, IL-18, tumour necrosis factor alpha (TNF-α) and high-sensitivity C-reactive protein (hs-CRP) levels were assessed in both groups. Results: Mean IL-6, IL-10, IL-18, TNF-α and hs-CRP in group A and group B was 6.57±3.53 and 2.73±1 (p≤0.001), 8.185±2.8 and 3.51±0.86 (p≤0.001), 136.31±89.0 and 47.96±9.76 (p≤0.001), 21.26±18.59 and 5.36±3.57 (p≤0.001), 4.69±6.3 and 2.63±2.22 (p≤0.008) respectively. On subgroup analysis mean TNF-α in subgroup Aa was 20.71±16.84, while in subgroup Ab was 7.56±1.93 (p≤0.001). Mean IL-10 in subgroup Ac and Ad was 8.74±3.29 and 7.47±1.82, respectively. Differences in levels of other cytokines in these subgroups were not found statistically significant. Conclusions: This study finds increased IL-6, IL-10, IL-18, TNF-α and hs-CRP levels in subjects with rheumatic mitral stenosis. Subjects with severe mitral stenosis had increased TNF-α levels. Subjects of mitral stenosis having pulmonary hypertension had increased IL-10 levels.